3D Detectors on Hydrogenated Amorphous Silicon for particle tracking in high radiation environment. (June 2020) - Menichelli, M; Boscardin, M; Crivellari, M; Davis, J; Dunand, S; Fanò, L; Moscatelli, F; Movileanu-Ionica, M; Petasecca, M; Piccini, M; Rossi, A; Scorzoni, A; et al.
Abstract: The vertex detectors for the future hadronic colliders will operate under proton fluencies above 10 16 p/cm 2 . Crystalline Silicon detector technology, up to now, has kept the pace of the increasing fluencies in the LHC era and it is still the prevalent vertex detector material for the present and for the immediate future. Looking ahead in time, an alternative solution for such a detector has to be found because for the future there is no guarantee that Crystalline Silicon will hold this challenge. For this reason the development of hydrogenated amorphous silicon vertex detectors based on 3D-technology have been proposed and the technological solutions in order to build these detectors are described in this paper.